2022
DOI: 10.1155/2022/3556372
|View full text |Cite|
|
Sign up to set email alerts
|

Apelin Alleviates Meniscus Endothelial Cell Apoptosis in Osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative disease characterized by articular cartilage and/or chondrocyte destruction, and although it has long been considered as a primary disease, the importance of meniscus endothelial cell modulation in the subchondral microenvironment has recently drawn attention. Previous studies have shown that apelin could potentially inhibit cellular apoptosis; however, it remains unclear whether apelin could play a protective role in protecting the endothelium in the OA meniscus. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Vascularization of this region is the most active while the other two zones are avascular to a different degree 105 . According to such heterogeneity in vascularity, scRNA‐seq discovered that endothelial cells played an important role in meniscus degeneration 106 . ECs (endothelial cells in meniscus) progenitors (marked with CD146+) can not only generate vessels to maintain a blood supply, but also promote the migration of meniscus cells.…”
Section: Elucidating Molecular Mechanisms Of Osteoarthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Vascularization of this region is the most active while the other two zones are avascular to a different degree 105 . According to such heterogeneity in vascularity, scRNA‐seq discovered that endothelial cells played an important role in meniscus degeneration 106 . ECs (endothelial cells in meniscus) progenitors (marked with CD146+) can not only generate vessels to maintain a blood supply, but also promote the migration of meniscus cells.…”
Section: Elucidating Molecular Mechanisms Of Osteoarthritismentioning
confidence: 99%
“…Prevent ECM degradation and promote reparative anabolic processes [72] Cartilage tissue from 10 OA patients CPCs Repair cartilage [53] HTC Human articular cartilage samples GPX4 Anti-ferroptotic effect of Trpv1 in OA cartilage [76] Human meniscus samples FCP Progenitors in OA meniscus [100] ALPN Antiapoptotic maintaining vascular activity in the red-zone of meniscus [106] Human subchondral bone samples Pre-ECs and EC Pathological angiogenesis coupling with aberrant osteogenesis to accelerate OA progression in the subchondral bone [113] Synovial joint tissue ACKR4 Decrease chondrocyte catabolism [85] Human F I G U R E 8 scRNA-seq links potential clinical applications with pre-clinical studies on OA. Singlecell RNA sequencing is a promising technology in preclinical studies to identify potential molecular mechanisms or targets in OA and will be applied as a fundamental method in all aspects of OA clinical studies in the future.…”
Section: Origins Candidates Biological Process Referencementioning
confidence: 99%
See 1 more Smart Citation
“…
This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:
…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%